Linear stability of two-dimensional flow to three-dimensional perturbations in a channel with a flexible wall - Sibanda, P.; Motsa, S.S.; Shateyi, S. (Archives of Mechanics, 2004)
In this paper we investigate the effects of three-dimensional disturbance waves on the stability of a two-dimensional channel flow with one compliant surface. The study exploits the multideck structure of the flow in the limit of large Reynolds numbers to make an asymptotic analysis of the flow and to derive linear neutral stability results. The study shows that for a flow over flexible surfaces, three-dimensional disturbances may be more unstable than two-dimensional modes for a given set of wall properties.